2017
DOI: 10.1371/journal.pone.0171293
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of metformin on energy metabolism and visceral fat volume through a possible mechanism of fatty acid oxidation in human subjects and rats

Abstract: ObjectiveMetformin is known to have a beneficial effect on body weight and body composition, although the precise mechanism has not been elucidated yet. The aim of this study is to investigate the effects of metformin on energy metabolism and anthropometric factors in both human subjects and rats.MethodsIn human studies, metformin (1500mg/day) was administered to 23 healthy subjects and 18 patients with type 2 diabetes for 2 weeks. Metabolic parameters and energy metabolism were measured during a meal toleranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 38 publications
3
78
2
4
Order By: Relevance
“…These findings suggest that either (a) metformin does not robustly activate AMPK, or (b) metformin increases FAO independently of AMPK. Other studies have reported elevated gene expression of markers of FAO and increased mitochondrial biogenesis in mice fed an HFD and treated with metformin, which would potentially lead to greater oxidative capacity. Metformin has also been shown to prevent HFD‐induced loss of PPAR‐α expression in mice, which may be indicative of enhanced FAO .…”
Section: Mechanism By Which Metformin May Affect Ihtag Contentmentioning
confidence: 93%
See 2 more Smart Citations
“…These findings suggest that either (a) metformin does not robustly activate AMPK, or (b) metformin increases FAO independently of AMPK. Other studies have reported elevated gene expression of markers of FAO and increased mitochondrial biogenesis in mice fed an HFD and treated with metformin, which would potentially lead to greater oxidative capacity. Metformin has also been shown to prevent HFD‐induced loss of PPAR‐α expression in mice, which may be indicative of enhanced FAO .…”
Section: Mechanism By Which Metformin May Affect Ihtag Contentmentioning
confidence: 93%
“…Metformin has also been shown to prevent HFD‐induced loss of PPAR‐α expression in mice, which may be indicative of enhanced FAO . Tokubuchi et al investigated the effects of 2 weeks' treatment with metformin on energy metabolism in healthy people and people with T2DM and concluded that metformin reduced fasting respiratory quotient, suggesting a shift in the utilisation of fat as a fuel after metformin treatment, which may be indicative of enhanced FAO. However, metformin also increased the postprandial respiratory quotient in both healthy and T2DM groups, suggesting enhanced aerobic glycolysis, which does not support enhanced FAO via AMPK …”
Section: Mechanism By Which Metformin May Affect Ihtag Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin's beneficial effects on energy metabolism include enhanced activity of carnitine palmitoyltransferase 1, an essential component of mitochondrial fatty acid oxidation. 48 Metformin also promoted restoration of mitochondrial membrane potential and reversal of mutationassociated alterations in energy metabolism in a model of Parkinson disease 49 and contributed toward the restoration of cellular energy by activating adenosine monophosphate-activated protein kinase. 50 Our preliminary data have indicated that the coadministration of metformin with cisplatin prevents the neuronal mitochondrial dysfunction that results from cisplatin treatment in a mouse model of CIPN.…”
Section: Preventing Cipn By Targeting Mitochondrial Pathways With Metmentioning
confidence: 99%
“…Although the exact mechanisms underlying these protective effects need to be delineated, it is likely that metformin acts via modulation of mitochondria‐dependent cellular metabolism. Metformin's beneficial effects on energy metabolism include enhanced activity of carnitine palmitoyltransferase 1, an essential component of mitochondrial fatty acid oxidation . Metformin also promoted restoration of mitochondrial membrane potential and reversal of mutation‐associated alterations in energy metabolism in a model of Parkinson disease and contributed toward the restoration of cellular energy by activating adenosine monophosphate‐activated protein kinase .…”
Section: Introductionmentioning
confidence: 99%